2015
DOI: 10.1111/resp.12541
|View full text |Cite
|
Sign up to set email alerts
|

Use of non‐pharmaceutical interventions to reduce the transmission of influenza in adults: A systematic review

Abstract: During seasonal influenza epidemics and pandemics, virus transmission causes significant public health concern. Reduction of viral transmission by non-pharmaceutical interventions (NPI) has a significant appeal and is often recommended. However, the efficacy of such interventions is unclear. A systematic literature review was undertaken to identify and evaluate the published literature on NPI efficacy to prevent human transmission of influenza virus in adults. Reviewers assessed the quality of eligible studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 42 publications
1
59
0
2
Order By: Relevance
“…At least two recent civilian-based, well-controlled studies have shown the efficacy of HW measures in decreasing influenza virus contamination of household surfaces, with a concomitant decrease in the number of influenza cases in Bangkok, Thailand (653,654). Consistent with these studies and with the concept of decreases in virus load and transmissibility via fomites, HW and HH practices have been found to provide a 55% reduction in the risk of transmission of respiratory viruses, including influenza viruses, in three recent large systematic reviews in the literature (642,643,714). Additionally, two recent studies of school-age populations have shown that HH interventions can reduce ILI and laboratory-confirmed influenza infection (655,656).…”
Section: Fomite-related Transmission Hand Washing and Hand Hygienementioning
confidence: 71%
“…At least two recent civilian-based, well-controlled studies have shown the efficacy of HW measures in decreasing influenza virus contamination of household surfaces, with a concomitant decrease in the number of influenza cases in Bangkok, Thailand (653,654). Consistent with these studies and with the concept of decreases in virus load and transmissibility via fomites, HW and HH practices have been found to provide a 55% reduction in the risk of transmission of respiratory viruses, including influenza viruses, in three recent large systematic reviews in the literature (642,643,714). Additionally, two recent studies of school-age populations have shown that HH interventions can reduce ILI and laboratory-confirmed influenza infection (655,656).…”
Section: Fomite-related Transmission Hand Washing and Hand Hygienementioning
confidence: 71%
“…These results may explain why seasonal influenza is not always controlled, despite implementation of hand washing and water gargling in school settings. Thus, because NPIs have been considered a single category, interpretation of efficacy was difficult (Aiello et al, 2010a, Aiello et al, 2012, Cowling et al, 2009, Simmerman et al, 2011, Smith et al, 2015), suggesting that NPIs should be evaluated individually. However, because this study was cross-sectional in design, cause-and-effect relationships could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combinations of NPIs with pharmaceutical intervention may be more effective than either alone. However, studies assessing the effectiveness of NPIs have yielded inconsistent results (Aiello et al, 2010a, Smith et al, 2015), which may be caused by poor statistical power due to sample size or selection bias. Alternatively, randomized controlled trials may not always reflect the natural setting of an influenza epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, they were the best performing intervention across populations, settings, and threats. Similarly, in a narrative review, MacIntyre et al (2015) drew on evidence from randomized community trials to conclude that face masks do provide protection against infection in various community settings, subject to compliance and early use. Differences in publication date, search strategy, and study selection criteria may explain the discrepancies among these reviews.…”
Section: Cost-effectiveness Of Interventionsmentioning
confidence: 99%